Investigation of the utilisation of modular construction in South Africa - Dupwa, Rufaro Patience (My University, 2018)
Abstract The subject of modular construction is largely known internationally. The extent, to which modular construction is used, is partly subject to the capabilities, facilities, expertise and skills available to the project team. Due to the scant use of modular construction systems in the SA industry, these factors might be found wanting. The limitation of the rudimentary approach to construction is an impediment to achieving efficiency and sustainability of construction projects. Additionally, the approach has delayed reaching the project targets and subsequently delays improving quality of life and national development. This study aims to investigate the utilisation of modular construction systems in SA construction industry, and to examine the causes of under-utilisation of modular construction systems by clients of the construction industry. The study is an exploratory study that collects qualitative data from experienced construction industry professionals, industry major clients and modular system manufactures/suppliers. Semi-structured interviews and questionnaires conducted with these stakeholders produced valuable qualitative and quantitative data on the concept and key findings were drawn from this input. The modular construction systems on the market and the causes of under-utilisation of modular construction by construction industry clients in SA are discussed. The transportation restraints, the inability of making changes onsite, and limited design options appeared to be most significant challenges of using modular construction systems based on the findings. Several recommendations aimed at increasing the utilisation of modular construction systems by construction industry clients in SA were proposed in this study which including eliminating transportation restraints, inability to make onsite changes and increasing the design options.
Keywords: Modular construction; Buildings, Prefabricated; Industrialized building